Intersubband photoluminescence from III-nitride multiple quantum wells - Carter, Dale (2012)
This report confirms the achievement of near infrared absorption at 1.865μm wavelength using FTIR (Fourier Transform Infrared Spectroscopy) at room temperature conditions for a GaN/Al(Ga)N multiple quantum well structure. It covers the processes undertaken to prepare each sample, the set up of the FTIR system, simulation to obtain each wave function and all measurements related to the structure.